2018
DOI: 10.1016/j.hbrcj.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of corroded bonded fully prestressed and conventional concrete beams

Abstract: Prestressed concrete is widely used in the construction buildings. And corrosion of steel is one of the most important and prevalent mechanisms of deterioration for concrete structures. Consequently the capacity of post-tension elements decreased after exposure to corrosion. This study presents results of the experimental investigation of the performance/behavior of bonded fully prestressed and conventional concrete beams, with 40 MPa compressive strength exposed to corrosion. The experimental program of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…This result is general and independent of the beam geometry. In Figure 8, the variation of the ultimate moment with the decrease of the tendon area obtained for the prestressed beam in the previous numerical example is compared with the experimental values obtained in [52] for a fully prestressed specimen. Despite the radical difference in geometry of the section and the fact that the AASHTO beam is connected to a reinforced concrete slab, the behavior is almost identical.…”
Section: Numerical Model Of the Sections Damaged By Corrosionmentioning
confidence: 97%
“…This result is general and independent of the beam geometry. In Figure 8, the variation of the ultimate moment with the decrease of the tendon area obtained for the prestressed beam in the previous numerical example is compared with the experimental values obtained in [52] for a fully prestressed specimen. Despite the radical difference in geometry of the section and the fact that the AASHTO beam is connected to a reinforced concrete slab, the behavior is almost identical.…”
Section: Numerical Model Of the Sections Damaged By Corrosionmentioning
confidence: 97%
“…Moawad et al [5] fabricated bonded fully PC beams with accelerated corrosion using electrochemical techniques. After flexural tests had been conducted, the results showed that the flexural strength had been reduced by up to 10%, and that the ductility and initial stiffness were reduced compared to the non-corroded specimens.…”
Section: Introductionmentioning
confidence: 99%